(untitled) (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this research is to determine the relationship between self-control and juvenile delinquency in students. The approach used is quantitative with a correlational type. The sampling technique was quota sampling with a sample size of 57 students. The instrument in this research uses a scale in the form of a questionnaire. The research results show that there is a negative and significant relationship between self-control and juvenile delinquency in students with a correlation coefficient of -0.795 with a sig value. (p) = 0.000 or p < 0.05, which means that the higher the self-control a student has, the lower his juvenile delinquency will be. Likewise, vice versa, the lower the self-control a student has, the higher the level of juvenile delinquency